TaRL-Based Instructional Differentiation to Optimize Understanding of Probability among High School Students with Heterogeneous Cognitive Profiles - Qotru Sa’adah; Desy Lusiyana; Tohir Makhmud (al-Afkar, Journal For Islamic Studies, 2025)
Observations in class X.9 revealed that 68% of students scored below the Minimum Mastery Criteria (KKM). This classroom action research aimed to improve students’ motivation and learning outcomes through the Teaching at the Right Level (TaRL) approach. The study was conducted in two cycles. The results indicated that the implementation of TaRL was effective in enhancing students’ academic achievement, with the average score increasing from 67.9 (pre-cycle) to 75.8 (cycle I) and 84.7 (cycle II). In addition, the percentage of students meeting the mastery criteria improved from 32% (pre-cycle) to 38% (cycle I) and 62% (cycle II). These findings suggest that the TaRL approach can improve students' understanding. However, TaRL may require more time when applied to students with low literacy skills. To address this limitation, teachers are encouraged to integrate TaRL with other instructional strategies, such as differentiated learning.